Komposit Berpenguat Struktur Karbon Aktif Kayu ( dari Kayu Eucalyptus-papuana) Zirkonia Sebagai Bahan Alternatif Pasak Dental - Subrata Gantini; Hapsari Milla; Bambang Sunendar Purwasasmita (Jurnal Material Kedokteran Gigi, 2013)
Metals, ceramics, and reinforced polymers have all been used as dental post material. “FRC post = Fiber Reinforced Composite Post is very popular at this moment. Many kinds of materials have been explored as fiber reinforcement for this type of post, including carbon. In this study, activated carbon is combined with zirconia (through sol-gel templating) and PMMA, as an alternative material for composite dental post. Activated carbon is extracted from Eucalyptus papuana wood, a natural resource that is very abundant and economical. Purpose, To make an activated carbon-reinforced zirconia composite structure, to study the suitable zirconia-precursor concentration in enhancing the mechanical properties of the post material to besimilar to the commercial composite post. Methods: Eucalyptus- papuana wood was pyrolyzed at 750°C,producing activated-carbon with tubular pores. The synthesized carbon was then combined with zirconia, using sol -gel templating at 4 different zirconia-precursor molarities. After calcination at 900°C, the activated carbon-zirconia structure was impregnated with PMMA. Morphological image of the transverse surface zirconia showedattachment on the tubular wall of activatedcarbon and the tubular pores and were evenly covered with PMMA. The 3-point bending test showed that all the zirconia- precursor concentrations failed to produce flexural strength in the range of commercial posts (450-1100 MPa), but all their elastic moduli are equal with commercial posts (8-50 GPa). The values of modulus of elasticity of this materialwere comparable to the commercial composite posts with the highest value of 24.247 GPa produced from 0.8 M precursor. The higher the precursor concentration, the higher the mechanical properties of the material. Conclusion:the composite PMMA reinforced with activated carbon-zirconia structure was established, the concentrations of the precursor 0.05, 0.1, 0.4, and 0.8 are correspondsto the modulus of elasticity ofcommercial composite post, but none of these concentrations could produce flexural strength equivalent to the commercial posts